PENGARUH MOTIVASI, PENGALAMAN DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI PT PERKASA INDAH NUSA JAYA - Zhuang, Vanness (LPPM Universitas Putera Batam, 2025)
This study aims to evaluate the extent to which motivation, work experience, and job stress influence employee performance at PT Perkasa Indah Nusajaya. A total of 103 respondents were selected using a non-probability sampling technique with a saturated sample approach. Data were collected through structured questionnaires and analyzed using several statistical methods including validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression, and coefficient of determination. Hypothesis testing was conducted using t-test and F-test. The findings reveal that motivation, work experience, and job stress have a significant simultaneous effect on employee performance. Furthermore, motivation and work experience positively and significantly impact performance, while job stress exerts a negative and significant influence. These results emphasize the importance for companies to enhance employee motivation and experience while minimizing job-related stress to improve overall performance.